Admission systolic blood pressure and outcomes in large vessel occlusion strokes treated with endovascular treatment. (26th April 2016) - Goyal, Nitin; Tsivgoulis, Georgios; Iftikhar, Sulaiman; Khorchid, Yasser; Fawad Ishfaq, Muhammad; Doss, Vinodh T; Zand, Ramin; Chang, Jason; Alsherbini, Khalid; Choudhri, Asim; Hoit, Daniel; Alexandrov, Andrei V; et al.
Abstract : Background and purpose: High admission blood pressure (BP) levels have been associated with lower recanalization rates after endovascular treatment (EVT) for patients with acute ischemic stroke (AIS) with emergent large vessel occlusion (ELVO). We sought to evaluate the association of admission BP with early outcomes in patients with ELVO treated with EVT. Methods: Consecutive patients with AIS presenting with ELVO in a tertiary stroke center during a 4-year period were prospectively evaluated. Admission systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured using automated cuff recordings. A blinded neuroradiologist calculated the final infarct volume (FIV) using standardized ABC/2 methodology. A favorable functional outcome (FFO) at 3 months was defined as modified Rankin Scale score of 0–2. Results: Our study population consisted of 116 patients with AIS (mean age 63±13 years, median NIH Stroke Scale score 17 points (IQR 14–21), median FIV 30 cm 3 (IQR 8–94)). Higher admission SBP correlated with higher FIV (r +0.225; p=0.020). Patients with FFO had lower admission SBP (151±24 mm Hg vs 165±28 mm Hg; p=0.010), while admission SBP levels were higher in patients who died during hospitalization (169±34 mm Hg vs 156±24 mm Hg; p=0.043). A 10 mm Hg increment in admission SBP was independently (p=0.010) associated with an increase of 12 cm 3 in FIV (95% CI 3 to 21) in multiple linear regression models adjusting for potential confounders. A 10 mm Hg increment in admission SBP was independently (p=0.012) associated with a lower likelihood of FFO at 3 months (OR 0.64; 95% CI 0.45 to 0.91) in multiple logistic regression models adjusting for potential confounders. Conclusions: Higher admission SBP is an independent predictor of increased FIV and lower likelihood of 3-month FFO in patients with ELVO treated with EVT.